Tax Compliance Behavior: Insights from Behavioral Economics Perspectives - Andi, Andi (Accounting Studies and Tax Journal (COUNT), 2024)
Tax compliance behavior is a complex issue that is influenced by various factors, including the fairness of the tax system, tax knowledge, individual attitudes, and social norms. This research aims to examine how the application of nudge theory, an approach from behavioral economics, influences tax compliance in various countries with different economic contexts. The research method used is a systematic literature review with the PRISMA approach, which involves identification, selection and analysis of relevant articles from international databases. The findings show that the effectiveness of nudges is highly dependent on the local social and economic context; in developed countries, nudges focusing on system fairness and trust in government tend to be effective, whereas in developing countries, adapting nudges to the local context is critical. The implications of this research emphasize the need for policies that consider each country's specific context to design more effective nudge-based interventions. The study also identified several limitations, including variations in study methodology and limited data from countries with low tax compliance. Future research is expected to explore more adaptive nudge designs and examine the impact of external factors such as the economic crisis on the effectiveness of nudges in increasing tax compliance.